Rural Development, Poverty Reduction and Environmental Growth in Sub-Saharan Africa - Cleaver, Kevin (World Bank, Washington, DC, 2012)
? This article outlines the role that the World Bank will play in supporting a modified rural development strategy for the Sub-Saharan Africa region: The Bank will be more selective in targeting countries for assistance in rural development programs, focusing on those that demonstrate commitment to appropriate agricultural policy and investment. It will expand its information, education and communication initiatives to help governments generate widespread commitment by their citizenry. Bank finance will increasingly be directed towards national sector or subsector programs. Through country assistance strategies, the bank would ensure that national education, health, nutrition, transport, water and economic policy programs provide support for rural and agricultural development. Natural resource management, forestry, and water projects will be evaluated to identify best practice, leading to proposals for replication. All ongoing and proposed Bank-assisted agriculture projects will be reviewed to identify changes that would enhance the positive impact on using and developing African capacity. A participatory preparation and implementation plan involving farmers will be developed for every agriculture project supported by the Bank. Safety nets for the rural and urban poorest would be established. The Bank and its affiliates would more actively support the worldwide liberalization of agricultural trade and discourage inefficient industrial country agricultural policies.